Emerging regulatory mechanisms and functions of biomolecular condensates: implications for therapeutic targets - Soyoung Jeon; Yeram Jeon; Ji-Youn Lim; Yujeong Kim; Boksik Cha; Wantae Kim (Signal Transduction and Targeted Therapy)
Abstract Cells orchestrate their processes through complex interactions, precisely organizing biomolecules in space and time. Recent discoveries have highlighted the crucial role of biomolecular condensates—membrane-less assemblies formed through the condensation of proteins, nucleic acids, and other molecules—in driving efficient and dynamic cellular processes. These condensates are integral to various physiological functions, such as gene expression and intracellular signal transduction, enabling rapid and finely tuned cellular responses. Their ability to regulate cellular signaling pathways is particularly significant, as it requires a careful balance between flexibility and precision. Disruption of this balance can lead to pathological conditions, including neurodegenerative diseases, cancer, and viral infections. Consequently, biomolecular condensates have emerged as promising therapeutic targets, with the potential to offer novel approaches to disease treatment. In this review, we present the recent insights into the regulatory mechanisms by which biomolecular condensates influence intracellular signaling pathways, their roles in health and disease, and potential strategies for modulating condensate dynamics as a therapeutic approach. Understanding these emerging principles may provide valuable directions for developing effective treatments targeting the aberrant behavior of biomolecular condensates in various diseases.